2021
DOI: 10.1002/nafm.10550
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Passive Integrated Transponder Tags in a Small‐Bodied Catfish

Abstract: Members of the freshwater catfishes (order Siluriformes) are capable of transintestinal expulsion of foreign bodies, including internally implanted tags, which can bias movement and survival estimates. We evaluated long‐term (120‐week) retention rates of passive integrated transponder (PIT) tags in a laboratory setting to assess potential tag loss in Stonecat Noturus flavus. The PIT tags were surgically implanted into the peritoneal cavity of fish (n = 157) ranging from 71 to 213 mm TL. We demonstrated that St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, D'Amico et al . ( 2021 ) used sutures to close PIT tagging incisions in the Stonecat Noturus flavus (Rafinesque 1818) and had survival rates of 89% over 840 days for regular 12 mm PIT tags and survival rates of 99% over 751 days for fish tagged with polymer‐coated 12 mm tags (Table 2 ). The results from the sutured vs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, D'Amico et al . ( 2021 ) used sutures to close PIT tagging incisions in the Stonecat Noturus flavus (Rafinesque 1818) and had survival rates of 89% over 840 days for regular 12 mm PIT tags and survival rates of 99% over 751 days for fish tagged with polymer‐coated 12 mm tags (Table 2 ). The results from the sutured vs .…”
Section: Discussionmentioning
confidence: 99%
“…A study on blackspotted topminnow Fundulus olivaceus (Storer 1845) reported similar findings, and also found PIT tags impacted neither gonadal development nor swimming kinematics (Clark, 2016 ). The authors successfully applied the same tagging technique to other small‐bodied fishes including flathead chub Platygobio gracilis (Richardson 1836) and Noturus flavus with success, supporting the view that the technique is applicable to other taxa (D'Amico et al ., 2021 ; Swarr, 2018 ). More broadly, the results of the studies included in Table 2 and the meta‐analysis suggest that the use of 12 mm or smaller PIT tags is appropriate for a number of small‐bodied species, provided that the PIT tags selected for use are no more than 17% of the fish's total length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, guidance for tagging madtoms has also become available (D’Amico et al. 2021; Schumann et al. 2021).…”
Section: Summary Of Progressmentioning
confidence: 99%
“…This marking and tagging information for the three largest North American ictalurids (Blue, Flathead, and Channel catfish) was well summarized at Catfish 2020 in a review by Neely et al (2021a), which provides useful guidance on the relative strengths and weaknesses of each method as it relates to various objectives in catfish science. Very recently, guidance for tagging madtoms has also become available (D'Amico et al 2021;Schumann et al 2021).…”
Section: Techniquesmentioning
confidence: 99%